IMPLEMENTASI PARIWISATA BERKELANJUTAN DALAM PENGELOLAAN DESTINASI WISATA ALAM PINUSSARI MANGUNAN - Eki Melina Widanti; Atika Nur Hidayah; Kenyo Kharisma Kurniasari (Jurnal Paradigma Multidisipliner (JPM), 2022)
Nature-based tourist destinations are often associated with ecotourism. However, not all of these destinations develop into ecotourism since some are exploited as mass tourist attractions, such as Pinussari Mangunan. Pinussari Mangunan is located in Forest Management Resort (RPH) Mangunan, a protected forest area. Therefore, the destination requires sustainable tourist management in terms of sociocultural, economic, and environmental aspects. This study determines the implementation of sustainable tourism in the management of the Pinussari Mangunan using UNWTO indicators on sustainable tourism. This study used a qualitative approach with a qualitative descriptive analysis method. This study found that the management of Pinussari Mangunan mostly adheres to the measures of sustainable tourism indicators. Of the three factors assessed, the economic and socio-cultural aspects obtained high scores, but the environmental aspects received moderate scores. Nonetheless, these three aspects require further attention, such as enhancing human resource quality, increasing supervision, and educating tourists about the environment.Keywords: nature-based tourism, tourism management, sustainable tourism, UNWTO indicators